Geometrické struktury a objekty z hlediska aplikací v mechanice - Ambrozková, Anna (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2020)
Diplomová práce se vztahuje na mechaniku kontinua a její provázání s vybranými směry moderní diferenciální geometrie, které se zabývají geometrickými strukturami a objekty. Jedná se především o tensory, bandly, variety a jety. První část je věnovaná samotné mechanice kontinua a jejímu popisu ve více oblastech, další se zabývají matematickými pojmy a jejich případnou aplikací v mechanice.

This Master's thesis relates to continuum mechanics and its connection with selected directions of modern differential geometry, which deal with geometric structures and objects. These are mainly tensors, bundles, varieties and jets. The first part is devoted to the mechanics of the continuum itself and its description in several areas, others deal with mathematical concepts and their possible application in mechanics.
Geometrical structures and objects from the point of view of their applications in mechanics
Keywords: mechanika kontinua; referenční konfigurace; tensory; variety; jety; hlavní bandly; konexe; grupy; continuum mechanics; reference configurations; tensors; varieties; jets; principal bundles; connections; groups